Advanced Symmetric Solid Oxide Fuel Cell with an Infiltrated K2NiF4-Type La2NiO4 Electrode - Yang, Guangming; Su, Chao; Ran, Ran; Tade, Moses; Shao, Zongping (American Chemical Society, 2014)
Advanced symmetric solid oxide fuel cells (SOFCs) with a reducible electrode were proposed. Specifically, La2NiO4 + La0.9Sr0.1Ga0.8Mg0.2O3-delta (LSGM) [or Sm0.2Ce0.8O1.9 (SDC)] composite electrodes were successfully fabricated by an infiltration method and tested for power generation. X-ray diffraction (XRD) results demonstrated there was no noticeable phase reaction between infiltrated La2NiO4 and LSGM (or SDC) scaffold, and scanning electron microscopy (SEM) analysis indicated that the La2NiO4 phase formed as nanoparticles that decorated the surface of the scaffold. Different from conventional symmetric SOFCs, the electrode material La2NiO4 of current cells was reduced under an anode atmosphere to form metallic nickel as a high active catalyst for fuel oxidation. After the reduction, the electrode morphology and geometric integrity were maintained for the infiltrated electrode. For thick electrolyte-supported symmetric SOFCs with infiltrated La2NiO4 electrodes, an attractive maximum power density of ~550 mW cm-2 was achieved at 800 °C operating on hydrogen fuel, significantly higher than similar cells with stable perovskite oxide electrodes, as reported in the literature. It suggested that the unreduced and reduced La2NiO4performed well as a cathode for the oxygen reduction reaction and as an anode for fuel electro-oxidation, respectively. In addition, a favorable operating stability was demonstrated for a symmetric SOFC with an infiltrated La2NiO4 electrode. It provides a new way for developing cost-effective SOFCs with huge application opportunities.